2023
DOI: 10.3390/ijms24065416
|View full text |Cite
|
Sign up to set email alerts
|

Advances of Apetala2/Ethylene Response Factors in Regulating Development and Stress Response in Maize

Abstract: Apetala2/ethylene response factor (AP2/ERF) is one of the largest families of transcription factors, regulating growth, development, and stress response in plants. Several studies have been conducted to clarify their roles in Arabidopsis and rice. However, less research has been carried out on maize. In this review, we systematically identified the AP2/ERFs in the maize genome and summarized the research progress related to AP2/ERF genes. The potential roles were predicted from rice homologs based on phylogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…As one of the largest TF families in plants, AP2/ERF (APETALA2/Ethylene Responsive Factor) plays indispensable roles in plant growth, development, hormone regulation, flavonoid synthesis, and especially in responses to various stresses ( Zhang et al., 2020 ; Qian et al., 2022 ; Qi et al., 2023 ). Recently, three AP2/ERF TFs were identified as positive regulators of the chalcone isomerase (CHI) gene that enhanced the accumulation of flavanones and flavones in citrus ( Zhao et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…As one of the largest TF families in plants, AP2/ERF (APETALA2/Ethylene Responsive Factor) plays indispensable roles in plant growth, development, hormone regulation, flavonoid synthesis, and especially in responses to various stresses ( Zhang et al., 2020 ; Qian et al., 2022 ; Qi et al., 2023 ). Recently, three AP2/ERF TFs were identified as positive regulators of the chalcone isomerase (CHI) gene that enhanced the accumulation of flavanones and flavones in citrus ( Zhao et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Plant hormones play an important role in plant growth and developmental processes [29][30][31]. Qi et al reported that OsEATB restricts the ethylene-induced enhancement of gibberellin responsiveness and promotes the branching potential of both tillers and spikelets in rice [32,33]. In the present study, the ethylene signaling pathway activator (Os04g0456900) was also shown to be significantly upregulated based on the results of RNA-seq analysis in the rice lines with ETV traits, and the sequence alignment results showed two amino acids inserted in the T461 genome compared to WYG genome.…”
Section: Ethylene May Play An Important Role In Etv Traits Of Ricementioning
confidence: 99%
“…Moreover, AP2/ERFs also play key roles in regulating plant responses to various biotic and abiotic stresses, including salinity, drought, temperature, and multiple pathogens (e.g. viruses, fungi, and bacteria) (Qi, et al 2023 ; Xie, et al 2019 ). AP2/ERF superfamily is traditionally considered to specifically exist in plants, until its orthologs have been identified in genomes of microbes, such as the cyanobacterium Trichodesmium erythraeum , the virus Enterobacteria phage Rb49 (Magnani, et al 2004 ; Wessler 2005 ).…”
Section: Introductionmentioning
confidence: 99%